Potentially actionable molecular alterations in particular related to poor oncologic outcomes in salivary gland carcinomas - Julia Pikul; Marcin M. Machnicki; Anna Rzepakowska; Natalia Winiarska; Agnieszka Chudy; Albert Moskowicz; Kacper Król; Łukasz Fus; Grażyna Kostrzewa; Tomasz Stokłosa (BMC Cancer, 2025)
Abstract Aim The study was designed to evaluate molecular alterations, relevant to the prognosis and personalized therapy of salivary gland cancers (SGCs). Materials and methods DNA was extracted from archival tissue of 40 patients with various SGCs subtypes. A targeted next-generation sequencing (NGS) panel was used for the identification of small-scale mutations, focal and chromosomal arm-level copy number changes. The final analysis included selected genes with potential actionable aberrations for targeted therapies and outcome predictions in 37 tumours’ samples. Results The follow-up of the SGCs study cohort revealed disease recurrence or metastasis in 19 patients and indicated poor individual outcomes. The mean disease-free survival (DFS) within the poor outcome group was 2.4 years, and the overall survival (OS) was 5.4 years. The DFS and OS of the remaining 18 patients with favourable outcomes were 8.3 years. The genes most frequently affected with aberrations were NF1 (n = 9, 24%) and TP53 (n = 8, 22%), with increased occurrence observed in the poor outcome group: NF1 (n = 6, 32%) and TP53 (n = 6, 32%). CDKN2A biallelic deletion was the most common copy number variation (n = 5), and was detected in 4 cases with identified disease relapse. TERT promoter mutation and amplification were found in myoepithelial carcinoma. A p.Ile35Thr mutation was discovered in CTNNB1 in two cases of adenoid cystic carcinoma. ERBB2 alterations were remarkable for SDC ex PA. Furthermore, TP53 mutation was established as a relevant negative prognostic factor for overall survival (p = 0,04). The analysis revealed potentially actionable genes in detected alterations in: MECA 100% (1/1), SDC 100% (7/7), AD 92% (11/12), Ca ex PA 82% (18/22), MECA 65% (20/31), AdCC 64% (9/14) and AcCC 0% (0/1). Conclusions SGCs are a heterogeneous group of malignancies with distinct molecular landscape that characterized by poor prognosis and inadequate treatment options. Nonstandard strategies might be beneficial for patients who suffer from salivary gland cancers. Wider utilization of NGS analysis may increase the opportunity for patients with those rare cancers to receive more precise, personalized therapy.